2020
DOI: 10.1001/jamanetworkopen.2020.20172
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Year Incidence and Mortality Trends in Upper and Lower Gastrointestinal Bleeding in Finland

Abstract: IMPORTANCE Epidemiological data on lower gastrointestinal bleeding (GIB) in the general population are sparse. OBJECTIVE To describe the incidence, recurrence, mortality, and case fatality rates of major upper GIB and lower GIB in the general population of Finland between 1987 and 2016. DESIGN, SETTING, AND PARTICIPANTS This prospective cohort study used data from the 1987 to the 2012 cycles of the National FINRISK Study, a health examination survey that was conducted every 5 years in Finland. Survey participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…UGIB was verified as a significant risk factor for 5-year mortality in our study, which was similar to findings from previous studies of elderly patients (10,13). UGIB itself poses harm to patients, and can result in a mortality rate of up to 16-24% (14)(15)(16). The harm to AIS patients is further magnified due to the poor condition of the patients themselves.…”
Section: Resultssupporting
confidence: 90%
“…UGIB was verified as a significant risk factor for 5-year mortality in our study, which was similar to findings from previous studies of elderly patients (10,13). UGIB itself poses harm to patients, and can result in a mortality rate of up to 16-24% (14)(15)(16). The harm to AIS patients is further magnified due to the poor condition of the patients themselves.…”
Section: Resultssupporting
confidence: 90%
“…These results build on the research of the outcomes following ECH. Our finding that ECH is associated with a 4% increase in mortality corroborates the case fatality rates reported in studies of gastrointestinal bleeding, the predominant form of ECH 4,30–32 . We found that almost 1 in 10 bleeding hospitalizations was for a nongastrointestinal bleeding event.…”
Section: Discussionsupporting
confidence: 90%
“…We observed a trend of decreasing lower GIB over the studied period. Studies showed variable results for the trends of lower GIB in the last decade [ 39 - 41 ]. Data on lower GIB in patients with liver disease are very scarce.…”
Section: Discussionmentioning
confidence: 99%